PERLINDUNGAN HUKUM TERHADAP PEMBERI WARALABA MEREK ATAS TIDAK DIBAYARNYA ROYALTI OLEH PENERIMA WARALABA DALAM PERJANJIAN WARALABA - Purba, Felix Martuah; Kumala, Yudha Cahya; Irhamsah, Irhamsah (SINERGI : Jurnal Riset Ilmiah, 2025)
Article 1338 paragraph 1 of the Civil Code concerning the principle of freedom of contract which states that all agreements made legally apply as law for those who make them. Therefore, the franchise cooperation agreement applies as law for the parties. In practice, even though the franchise agreement has been made in a notarial deed, the franchisee defaults on royalty payments in the franchise agreement, this of course results in losses for the franchiser. The problem formulation in this research is what are the legal consequences for brand franchisees for non-payment of royalties to the franchisor in the franchise agreement? And what is the legal protection for brand franchisors for non-payment of royalties by franchisees in franchise agreements? The theories used in this research are the theory of legal consequences according to R. Soeroso and the theory of legal protection according to Satijipto Rahardjo.The method used in this research is normative juridical research in the form of library legal materials or secondary data with primary, secondary and tertiary sources of legal materials. The research approach used is statutory, conceptual, analytical and case approaches as well as techniques for collecting legal materials by identifying and inventorying positive legal rules, book literature, journals and other sources of legal materials. The analysis technique for legal materials is carried out using systematic legal interpretation, grammar and analogy construction. The research results show that the legal consequences for brand franchisees of non-payment of royalties to the franchisor in the franchise agreement are that the franchise agreement can end, where the franchisor will cancel the cooperation agreement and ask the franchisee to stop selling the product. In addition, the franchisee is obliged to pay royalty fees as compensation for the use of the franchisor's IPR to run the franchise business as agreed in the franchise agreement.  Legal protection for the brand franchisor for non-payment of royalties by the franchisee in the franchise agreement is in the form of repressive protection, where the franchiser has the right to give a warning either verbally or in writing in the form of a summons. Meanwhile, if this does not provide a solution, the franchiser has the right to file a lawsuit through the District Court against the franchisee who does not pay royalties, so that the franchisor as the injured party can recover all his rights and compensation for non-payment of royalties by the franchisee